2013
DOI: 10.5665/sleep.3210
|View full text |Cite
|
Sign up to set email alerts
|

Circulating FABP4 and FABP5 Levels Are Differently Linked to OSA Severity and Treatment

Abstract: FABP4 is directly associated with obstructive sleep apnea severity and did not change with continuous positive airway pressure treatment, while FABP5 was not associated with obstructive sleep apnea severity and increased with continuous positive airway pressure treatment. FABP4 and FABP5 have different associations with obstructive sleep apnea. FABP4 but not FABP5 could be considered a marker of metabolic alterations in obstructive sleep apnea patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The results showing distinct independent associations of increased FABP4 level with female gender, waist circumference as an index of adiposity, renal dysfunction indicated by low eGFR, and hypertriglyceridemia were in agreement with results of previous studies showing the same associations in a general population and in patients with several metabolic disorders ( 13 , 14 , 22 , 23 ), though the correlations were not strong probably due to the modulation of several concomitant drugs for diabetes mellitus, dyslipidemia and hypertension in the present study as a real-world setting. It has been shown that circulating FABP5 exists at levels of about a half or less of circulating FABP4 ( 14 , 32 34 , 42 , 43 ), as was confirmed in the present study. It has been shown that FABP5 concentration are related to several metabolic markers, though the correlation is not stronger than that of FABP4 ( 14 , 33 , 34 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showing distinct independent associations of increased FABP4 level with female gender, waist circumference as an index of adiposity, renal dysfunction indicated by low eGFR, and hypertriglyceridemia were in agreement with results of previous studies showing the same associations in a general population and in patients with several metabolic disorders ( 13 , 14 , 22 , 23 ), though the correlations were not strong probably due to the modulation of several concomitant drugs for diabetes mellitus, dyslipidemia and hypertension in the present study as a real-world setting. It has been shown that circulating FABP5 exists at levels of about a half or less of circulating FABP4 ( 14 , 32 34 , 42 , 43 ), as was confirmed in the present study. It has been shown that FABP5 concentration are related to several metabolic markers, though the correlation is not stronger than that of FABP4 ( 14 , 33 , 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, the results showing that circulating levels of FABP4 and FABP5 were independent predictors of each other are reasonable. Previous studies also revealed a positive correlation between concentrations of FABP4 and FABP5 in several populations ( 32 34 , 42 , 43 ).…”
Section: Discussionmentioning
confidence: 62%
“…Similar findings had been observed in humans, where circulating AFABP concentration was associated with increasing lobular inflammation, hepatocyte ballooning and higher stages of hepatic fibrosis on liver histology ( 94 ). On the other hand, elevated serum AFABP concentration was also found in patients with severe OSA compared with those with milder disease ( 95 , 96 ), and the use of continuous positive airway pressure was shown to reduce circulating AFABP concentrations in a recent randomized controlled study ( 97 ). Moreover, circulating AFABP was associated with adverse renal outcomes including renal deaths in patients with type 2 diabetes ( 98 ), which could possibly be a result of macrophage infiltration in the glomerulus and interstitium, ectopic expression of AFABP in the glomerulus, as well as AFABP induced increased ER stress in the mesangial cells ( 99 101 ).…”
Section: Afabp and Other Obesity-related Conditions With Increased Cardiovascular Riskmentioning
confidence: 99%
“…In addition to the cytoplasm, FABP4 can also be released into the circulation. Elevated levels of FABP4 in the circulation were found in many diseases, such as bronchopulmonary dysplasia, SLE (systemic lupus erythaematosus) patients and OSA (obstructive sleep apnoea) [ 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%